Efeito da suplementação com "Ração humana light" nos fatores determinantes da Síndrome metabólica - Oliveira, Anna Júlia Ferreira Vaz de (2012)
The "human light diet" is a flour rich in fiber. Studies in subjects with metabolic syndrome suggest that consumption of fiber, as a food supplement, can help regulate their determinants. It is characterized by the association of hypertension, abdominal obesity, glucose intolerance, hypertriglyceridemia and low blood concentrations of high density lipoprotein. Based on these facts and considering that in the current literature found no studies involving the use of the human diet with the metabolic syndrome, showing its effectiveness. The aim of this study was to evaluate the impact of diet supplementation with human factors in the metabolic syndrome. The sample consisted of 28 adult women with a confirmed diagnosis of metabolic syndrome, divided into two groups: intervention group for eight weeks supplementation with 30 grams daily human diet (n = 14) and a control group without supplementation (n = 14). At first, patients were interviewed. They were then subjected to an initial anthropometric (waist circumference, height and weight) and blood pressure. Blood test for analysis of biochemical variables was performed at University Hospital Lauro Wanderley-UFPB. A reevaluation of anthropometric, blood pressure and was performed 60 days after intervention. The two-factor ANOVA was used to evaluate the anthropometric data, blood pressure and blood chemistries. We adopted p <0.05 for statistical significance. The final sample consisted of 16 obese adult women, mean age 29.5 ± 7.8 years and body mass index of 106.91 ± 7.48 kg/m2 Comparison between groups post intervention can be observed that body weight, waist circumference and systolic blood pressure were significantly lower in the intervention group. Supplementation with human diet for eight weeks can be a good alternative for people who aim to lose weight and regulate blood pressure. However the treatment of metabolic syndrome in human diet should be encouraged and further studies, controlled epidemiological, performed to assess the benefits and risks of long-term supplementation in individuals with different age groups.